115k views
7 votes
The solution set of the inequality 2x - y> 2 consists of all the points_?_ the line?

above; y = 2x - 2
below, y = 2x - 2
above; y = -2x + 2
below; y = -2x + 2

User Spondbob
by
4.9k points

1 Answer

8 votes

Answer:

The answer is below, y = 2x - 2

Explanation:

2x - y > 2

-2x -2x

-y > 2 - 2x

/-1 / -1

y < -2 + 2x, also written as y < 2x - 2

This is where we got our answer: y = 2x - 2

*There is an invisible 1 before the variable (y)*

*When dividing an inequality with a negative number, the sign flips (from < to >, or from ≤ to ≥)*

I'm going to share a little tip:

< or ≤ = below the line

> or ≥ = above the line

Hope that helps

User Mani David
by
5.6k points